2014
DOI: 10.4303/jdar/235841
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Behavioral Consequences of Prenatal Binge Toluene Exposure in Adolescent Rats

Abstract: The continued abuse of inhaled organic solvents, especially among women of childbearing age, raises the risk of long-term behavioral effects of maternal toluene abuse. In this study, the effects of short-term exposures to high toluene concentrations (i.e., "binges") were tested in independent groups of adolescent rats with different toluene treatments: (a) acute: 30-day-old animals exposed for 30 min to air (A) or 6,000 ppm toluene (T); (b) prenatal and postnatal: rats exposed to T or A from gestation days 8-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
1
0
0
Order By: Relevance
“…These observations are compatible with findings by Hass et al ( 1995 , 1999 ) who showed that the mnemonic processes are particularly vulnerable to xylene and toluene effects. Additionally, similar results have been demonstrated by other experimental tests (i.e., the object recognition test and the Morris water maze task), which involve short-term memory or spatial learning (Fifel et al, 2014 ; López-Rubalcava et al, 2014 ; Callan et al, 2015 ). No mechanistic studies have been designed to find out the molecular targets implicated in cognitive impairments, but changes in the expression of NMDA receptor (subunits NR1 and NR2 mRNA), NMDA receptor antagonism, and inhibition of neurogenesis in the hippocampus could be associated with the impaired memory observed in mice exposed to thinner during gestation (Seo et al, 2010 ; Huerta-Rivas et al, 2012 ; Win-Shwe and Fujimaki, 2012 ).…”
Section: Discussionsupporting
confidence: 78%
“…These observations are compatible with findings by Hass et al ( 1995 , 1999 ) who showed that the mnemonic processes are particularly vulnerable to xylene and toluene effects. Additionally, similar results have been demonstrated by other experimental tests (i.e., the object recognition test and the Morris water maze task), which involve short-term memory or spatial learning (Fifel et al, 2014 ; López-Rubalcava et al, 2014 ; Callan et al, 2015 ). No mechanistic studies have been designed to find out the molecular targets implicated in cognitive impairments, but changes in the expression of NMDA receptor (subunits NR1 and NR2 mRNA), NMDA receptor antagonism, and inhibition of neurogenesis in the hippocampus could be associated with the impaired memory observed in mice exposed to thinner during gestation (Seo et al, 2010 ; Huerta-Rivas et al, 2012 ; Win-Shwe and Fujimaki, 2012 ).…”
Section: Discussionsupporting
confidence: 78%